Dilación del desove de Modiolus capax (Bivalvia: Mytilidae) - Claudia Farfán; Ana María Espinoza Peralta; Olivia Tapia Vázquez (Revista de Biología Tropical, 1998)
La capacidad de Modiolus capax de dilatar el desove y retener gametos maduros por períodos largos se estudió en organismos sexualmente maduros sometidos a condiciones de baja temperatura y raciones alimenticias superiores a las de mantenimiento. La efectividad del tratamiento se verificó mensualmente y se contrastó con la condición reproductiva de los organismos en el medio natural. En el lote experimental no se registraron desoves expontáneos y aunque los índices de condición general y gonadosomático se mantuvieron consistentemente mejores que en el medio natural, para la octava semana de tratamiento las gónadas ya presentaban evidencias de reabosorción. Se postula que las caracterísitcas del ciclo reproductivo natural, desove masivo en verano y reposo a fines de otoño y pricipios de invierno, limita la capacidad del mítilido de retener gametos maduros por períodos prolongados. The capacity of Modiolus capax to delay spawning and to hold mature gametes for long periods, was analyzed in sexually mature organisms subjected to cold water and food rations higher than those for maintenance. The experimental group, 200 mussels collected in August from Bahia de los Angeles, Baja California, Mexico, was subjected to 19±2 °C, temperature comparable to that in the natural environment during autumn and early winter; the daily food rations, delivered in open flow, were equivalent to 0.5-1.0% of the mussel’s dry soft body weight. The effectiveness of the experimental treatment was verified every month in a sample of 16 mussels; for contrast, a sample from Bahia de los Angeles was also analyzed. The assessed variables were general condition and gonadosomatic indices and for the histological study of the gonads, a maturity scale with eight stages was designed. In September the mussels from the natural environment were in the initial phase of post-spawning; by December they were in late post-spawning or rest. In the experimental group there were no spontaneous spawnings and general condition and gonadosomatic indices remained consistently higher than in the natural environment, however, by the eight-week of treatment the gonads showed evidences of incipient reabsorption. It is proposed that the natural reproductive cycle, mass spawning in summer and rest in late autumn and early winter, might be limiting the mussel’s capacity to retain mature gametes.